PETROLOGY OF THE INJANA FORMATION (UPPER MIOCENE)AT ZAWITA, AMADIYA AND ZAKHO AREA, NORTHERN IRAQ - Y. Tamar-Agha, Mazin; A. Salman, Noor (Iraqi Journal of Science, 2023)
This study deals with the petrology of Injana Formation (Upper Miocene) atZawita, Amadia and Zakho areas. The sandstone of Injana Formation is of twotypesnamely, litharenite and feldspathiclitharenite. The rock fragments of InjanaFormation are mostly sedimentary and hence the sandstones are classified assedarenite and more specifically chertarenite owing to the predominance of chertrock fragments. The sandstone is mineralogicallysubmature rangingfrommechanically and chemically stable tounstable. The petrographic studies revealnearness of source area with arid to semi-arid climate. The source rocks aresedimentary, low- to medium-grade metamorphic and basic volcanic rocks. They aremostly supplied from the rising mountain farther north and east (Taurus and ZagrosRanges) during the Alpine Orogeny induced by the continent-continent collisionbetween Arabia and Eurasia.The mudstone consists of mixture of clay and silt withvariable percentages. The major clay minerals are chlorite, kaolinite and mixed-layerillite-smectite. The non-clay minerals are calcite, quartz and subordinate feldspars.